Features of comprehensive control in the preparation of basketball players - Losin B.E. B.E.; Minina L.N.; Sergazinova M.A.; Grigoryeva D.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to expert assessment of complex control over the training of basketball players at the stage of improving sportsmanship. Methods and structure of the study. The method of expert assessment of 81 basketball coaches was used. The respondents had extensive practical work experience and high qualifications. The questionnaire contained questions regarding the content and organization of comprehensive control during the training of basketball players. Results and conclusions. As a result of the method of interviewing highly qualified experts, problematic aspects of complex control over the level of preparedness of players in modern basketball were identified. It was revealed that the assessment of important sections of basketball players’ preparedness (hand speed, jumping speed, special agility, etc.) requires the development of new ones and clarification, taking into account the modern realities of basketball, of existing methods, indicators and criteria of preparedness. It has been established that the system of comprehensive control over the level of preparedness of basketball players has not yet been fully formed. Additional research is required on the scientific substantiation of the content, methods, tests (control exercises) for assessing the level of preparedness of basketball players. The greatest difficulties for trainers are in carrying out operational control.